Acceptance of the Implementation of a Smart Campus Based on 5g Technology by the University S Constituents - Soto-Gomez, J; Palominos-Belmar, P (Institute of Electrical and Electronics Engineers Inc., 2021)
This work systematises the requirements of users circulating in the different spaces of a university campus that can be resolved through the services offered by 5G. The methodology is based on the application of surveys to the different actors that interact on university campuses in three South American countries, in order to focus efforts in each country. © 2021 IEEE.